2015
DOI: 10.1038/srep16910
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidum polysaccharide peptide prevents renal ischemia reperfusion injury via counteracting oxidative stress

Abstract: Ganoderma lucidum polysaccharide peptide (GLPP) scavenges oxygen free radicals that are a key factor in the pathogenesis of renal ischemia reperfusion injury (RIRI). The aim of this study was to determine whether GLPP could attenuate RIRI by counteracting the oxidative stress. The mechanism involved was assessed by an in vivo mouse RIRI model and an in vitro hypoxia/reoxygenation model, and tunicamycin-stimulated NRK-52E cells were used to explore the GLPP-mediated alleviation of ER stress. Experimental result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 55 publications
(55 reference statements)
2
45
0
2
Order By: Relevance
“…To measure the amount of lipid peroxidation, mRTECs were collected for detection of superoxide dismutase (SOD) and malondialdehyde (MDA) activities using specific assay kits (Beyotime) according to the manufacturer's instructions …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure the amount of lipid peroxidation, mRTECs were collected for detection of superoxide dismutase (SOD) and malondialdehyde (MDA) activities using specific assay kits (Beyotime) according to the manufacturer's instructions …”
Section: Methodsmentioning
confidence: 99%
“…Renal ischaemia reperfusion injury (RIRI), regarded as a risk factor for transplanted kidneys, is a hallmark and significant causative factor of AKI . During the process of RIRI, a sequence of events occur, such as the renal tubular epithelial cells apoptosis and necrosis, the accumulation of reactive oxygen metabolites, calcium overload, as well as the increasing number of NO, inflammatory mediators and energy metabolism disorder and so on. It will result in kidney function disorder thus causing metabolic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…The previous study reported that natural substance having high antioxidant activity and free radical scavenging activity effectively eliminates the urea and creatinine through excretion and decreases the serum urea and creatinine level (Mehrdad et al, 2007). It has also been reported that mushroom belongs to Ganoderma have high antioxidant capacity and their supplements reduced renal pathology by decreasing serum urea and creatinine concentration (Zhong et al, 2015;Abdullah et al, 2018). Uric acid is the end product of endogenous purine metabolism and its production and metabolism involving various factors that regulate hepatic production, renal and gut excretion of this compound (Simao et al, 2012).…”
Section: Groups Of Ratsmentioning
confidence: 99%
“…GLPP is one of the major pharmacological constituent of Ganoderma lucidum and has diverse bioactivities [15]. Our previous study revealed that GLPP prevented renal ischemia reperfusion injury via counteracting oxidative stress [10]. Besides, a randomized, doubleblind placebo-controlled crossover study indicated that polysaccharide peptides enriched Ganoderma lucidum possessed antioxidation and hepatoprotection in healthy volunteers [16].…”
Section: Introductionmentioning
confidence: 99%
“…Ganoderma lucidum has been widely used for prevention and treatment of various medical diseases including cancer [6,7], liver damage induced by hepatotoxic drugs [8,9], kidney injury [10], specifically for metabolic diseases such as diabetes [11], obesity [12], and other cardiovascular syndromes [13]. Ganoderma lucidum polysaccharide peptide (GLPP), a group of extract from Ganoderma lucidum (Leyss ex Fr.)…”
Section: Introductionmentioning
confidence: 99%